Investigating The Determinants of Islamic Bank’s Profitability: A Cross Countries Analysis - Rindang Nuri Isnaini Nugrohowati; Muhammad Hamdan Syafieq bin Ahmad; Faaza Fakhrunnas (Muhammadiyah University Press, 2022)
The measurement of bank profitability has an essential role in the banking sector’s success and is an indicator for predicting financial distress. This study aims to look at the determinants of the profitability of Islamic banks by including the bank’s internal and macroeconomic variables. The study focuses on Islamic banking in 10 countries with the most prominent Islamic finance sector during the 4th quarterly data period from 2016 to the 4th quarter of 2021. The data analysis method in this study uses panel data fixed effect model analysis. The results showed that the bank’s internal variables, namely bank size, capital adequacy, liquidity, and banking stability, are important factors that affect profitability. Interesting findings show that increased financial inclusion variables and labor productivity can encourage high profitability growth. Meanwhile, GDP and inflation also affect banking performance from the macro sector. The study implies that Islamic bank needs to manage the internal financial condition properly to achieve and maintain the performance. In addition, to increase the performance the bank needs to heighten the human resources capacity while the financial authorities are required to issue the policies to support the development of Islamic banks.